1998
DOI: 10.1097/00004694-199801000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: From 1991 to 1994, 375 supracondylar fractures had percutaneous pinning after closed or open reduction. Nineteen of these with normal preoprative neurologic examinations had postoperative ulnar nerve palsies. All but two of the 19 were followed up. These 17 patients had complete return of function. Only four of the 17 had the medial pins removed, and two others had explorations, which showed no interruption of the nerve. Many of these patients did not have complete return of function until after 4 months. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Data pooled from 1455 patients found that the incidence of ulnar nerve iatrogenic injury was 5.04 times higher in medial/lateral wire fixation compared to lateral entry fixation [11]. There is also concern about delayed iatrogenic nerve injury using medial wires [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data pooled from 1455 patients found that the incidence of ulnar nerve iatrogenic injury was 5.04 times higher in medial/lateral wire fixation compared to lateral entry fixation [11]. There is also concern about delayed iatrogenic nerve injury using medial wires [23]. …”
Section: Discussionmentioning
confidence: 99%
“…On placing medial wires, surgeons may choose to use a closed, miniopen, or open technique depending on their level of experience and current practice. Advocates of the crossed wire technique state this may convey increased biomechanical stability but the ulnar nerve is at risk from the medial wire [15, 16]. With lateral entry only, iatrogenic injury to the ulnar nerve should be avoided but the construct may be biomechanically less stable [1720].…”
Section: Introductionmentioning
confidence: 99%
“…Ulnar nerve palsy after percutaneous cross-pinning of supracondylar fractures [9] and after trampoline injuries [10] have also been reported but, to the best knowledge of the authors, this is the first case reported in the literature which documents a case of ulnar nerve injury due to comminuted fracture of the humerus shaft.…”
Section: Discussionmentioning
confidence: 99%
“…A routine surgical exploration of the nerve is not recommended, but an incision over the medial epicondyle may to be useful in order to detect the ulnar groove and facilitate correct pin placement (Yen and Kocher 2008). Nevertheless, damage to the ulnar nerve is a well-known complication and affects between 2% and 20% of patients treated with crossed fixation (Lyons et al 1998). We can confirm the high rate of ulnar nerve injuries after treatment with crossed pinning.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been reported, but crossed pinning with postoperative immobilization is the preferred technique (Brauer et al 2007, Kocher et al 2007, Zamzam and Bakarman 2009). Iatrogenic injury to the ulnar nerve has been described in up to 20% of the cases treated with crossed pinning (Lyons et al 1998). In addition, radial pinning may damage the radial and anterior interosseous nerve (Brauer et al 2007, Kocher et al 2007, Omid et al 2008).…”
mentioning
confidence: 99%